Analysis of the Influence of Fear of Missing Out, Sales Promotions, E-Wallets, Flash Sales, and Hedonistic Shopping Motivation on Impulsive Buying of Sea Makeup Bundling Products on the TikTok Shop Platform (Study of the Purwokerto Community) - Suci Yuliana Sari; Herni Justiana Astuti; Dian Widyaningtyas; Purnadi Purnadi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the influence of Fear of Missing Out (FoMO), sales promotions, e-wallets, flash sales, and hedonistic shopping motivation on impulsive purchases of 3-in-1 Beauty Essential Sea Makeup bundled products on the TikTok Shop platform. This study uses a quantitative approach with purposive non-probability sampling techniques on 156 respondents from Purwokerto who have made impulsive purchases. Data analysis was performed using SEM-PLS through the SmartPLS version 4.1.1.6 application. The results showed that sales promotions and hedonistic shopping motivation had a positive and significant effect on impulsive buying, while FoMO, e-wallets, and flash sales did not have a significant effect on impulsive buying. This study provides a theoretical contribution by extending the application of Social Cognitive Theory (SCT) within the context of social e- commerce, particularly in the marketing of the 3-in-1 Beauty Essential Sea Makeup bundling product on TikTok Shop, by demonstrating how the interaction between personal factors, the environment, and the ease of transaction systems simultaneously shapes consumers’ impulsive buying behavior.